Do Both U.S. and Foreign Macro Surprises Matter for the Intraday Exchange Rate? Evidence from Japan - Rasmus Fatum; Michael Hutchison; Thomas Wu (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
We investigate the effects of both U.S. and Japanese news surprises, measured as the difference between macroeconomic announcements and preceding survey expectations, on the intraday JPY/USD exchange rate. No previous study has considered the intraday JPY/USD exchange rate responses to a broad set of comparable news surprises from both the U.S. and Japan. We show that news surprises from Japan are as influential as those from the U.S. in moving 5-minute JPY/USD exchange rate returns and, therefore, focusing on U.S. news while disregarding foreign news misses half the story. Our results also show that distinguishing between positive and negative news surprises and the state of the Japanese business cycle is important in understanding the link between exchange rates and news.
Keywords: F31; G15; C22; 330; Foreign Exchange Rates; Intraday Data; Macroeconomic News Effects; Wechselkurs; Ankündigungseffekt; Konjunktur; Japan; USA